OXYGEN ISOTOPIC SIGNATURE OF 4.4-3.9 GA ZIRCONS AS A MONITOR OF DIFFERENTIATION PROCESSES ON THE MOON - Nemchin A.A.; Whitehouse M.J.; Pidgeon R.T.; Meyer C. (My University, 2006)
We report oxygen isotopic compositions for 14 zircon grains from a sample of sawdust from lunar breccia 14321. The zircons range in age from ?4.4 to 3.9 Ga and in U and Th content from a few to several hundred ppm. As such these grains represent a range of possible source rocks, from granophyric to mafic composition, and cover the total age range of the major initial lunar bombardment. Nevertheless, results show that the oxygen isotopic compositions of the zircons fall within a narrow range of ?18O of about 1 per mil and have ?18O values indistinguishable from those observed for terrestrial mid-ocean ridge basalts confirming the coincidence of lunar and Earth oxygen isotopic compositions. In the ?17O vs. ?18O, coordinates data form a tight group with a limited trend on the terrestrial fractionation line. The zircon oxygen isotopes show minimal evidence of the extreme and variable mineral differentiation and element fractionation that have contributed to the formation of their parent rocks. ? 2006 Elsevier Inc. All rights reserved.
Keywords: DIFFERENTIATION; MOON; OXYGEN ISOTOPE